1988
DOI: 10.1002/glia.440010204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidic and basic fibroblast growth factors (aFGF and bFGF) on the proliferation and the glutamine synthetase expression of rat astroblasts in culture

Abstract: The two fibroblast growth factors called acidic and basic FGF (aFGF and bFGF) show a strong homology (55%) of their amino acid sequence (Esch et al.: Proc. Nat. Acad. Sci. USA 85:6507-6511, 1985). The effects of these factors on the rate of proliferation of rat astroblasts and on the expression of glutamine synthetase activity in cells grown in primary culture were investigated and compared under various culture conditions. In all the experimental conditions used, both growth factors triggered the proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 44 publications
5
54
0
Order By: Relevance
“…These results corroborate some of our previous results on astroblast proliferation and maturation obtained in various conditions [21,28]. Although the analyses of the autoradiograms have been done visually, the main result which is a similarity between the effects of aFGF and bFGF cannot be disputed since, with the same technical approach, in a previous work we have shown that epidermal growth factor and thrombin modulated the synthesis of many proteins differently than aFGF [20].…”
Section: Discussionsupporting
confidence: 90%
“…These results corroborate some of our previous results on astroblast proliferation and maturation obtained in various conditions [21,28]. Although the analyses of the autoradiograms have been done visually, the main result which is a similarity between the effects of aFGF and bFGF cannot be disputed since, with the same technical approach, in a previous work we have shown that epidermal growth factor and thrombin modulated the synthesis of many proteins differently than aFGF [20].…”
Section: Discussionsupporting
confidence: 90%
“…Some of these effects with bFGF have been reported previously (Perraud et al, 1988). Effects of bFGF were evident after 24 h and were complete within 48 h, affecting all GFAP ϩ cells in the culture, as seen in Figure 1B.…”
Section: Effects Of Bfgf On Morphology Of Ca1/ca3 Hippocampal Astrocytessupporting
confidence: 78%
“…We have identified basic fibroblast growth factor (bFGF) as a potent inducer of process growth and membrane retraction in cultured astrocytes (see also Perraud et al, 1988). By expressing dominant inhibitory or constitutively active forms of the Ras family members, we have defined a signal transduction cascade in which bFGF, acting via Ha-Ras, inhibits Rac1 and RhoA.…”
Section: Introductionmentioning
confidence: 99%
“…7), again showing differential signal transduction for the apoE/HDL release by a P13K/Akt pathway and lipid biosynthesis by an MEK/ ERK pathway. DISCUSSION FGF-1 is a stimulant for proliferation and cell differentiation of mesodermal and neuroectodermal cells such as fibroblasts and astrocytes (35). Most studies of this factor have focused on its activity in promoting cell growth and differentiation.…”
Section: Fgf-1 Regulation Of Biogenesis Of Apoe-hdl In Astrocytesmentioning
confidence: 99%